Interpretable machine learning for optimizing computer system - Chen, Peilin (Nanyang Technological University, 2024)
Exploration of PRIMO - A Unified Framework of Interpretable Models on Learning Augmented Systems. In this report, in addition to the findings presented in PRIMO's original paper, more experimental details on case studies of Clara and Pensieve are elaborated. Moreover, further hyperparameter tuning and generalisation ability testing are undertaken to examine and enhance the performance of the model in each case study